A Model for Analyzing and Measuring the Performance of Industrial Enterprises - Tomić, Miloš; Tešić, Zdravko; Kuzmanović, Bogdan; Tomić, Ivana (International Journal of Industrial Engineering and Management, 2015)
This research has attempted to use tool for action plan selection (TAPS) software, analytic hierarchy process (AHP) software and to use new developed software for defining performance indicators and how it could be used by managers to construct a performance measurement system. In this research, we used a process model of the organization, suitable for displaying a combination of input, process and output measures. Besides, new software for data collection, analysis and visualization of key performance indicators and their impact on the performance of the firm performance is developed. The empirical part of study is based on thirty interviews from ten case manufacturing and service organizations. Article history: Received (25.09.2014); Revised (12.01.2015); Accepted (02.03.2015)